The Bibionidae (Diptera) from Morocco, with description of four new species - Haenni, Jean-Paul; Kettani, Kawtar (Zootaxa, 2026)
Based on recent material mainly collected in the Rif region, a critical review of the fauna of Bibionidae of Morocco is presented. Four species, Bibio ebejeri sp. nov., B. kedrocharis sp. nov., B. longitarsis sp. nov. and B. ponti sp. nov. are described as new. Five species, Bibio anglicus Verrall, 1869, B. clavipes Meigen, 1818, Dilophus bispinosus Lundström, 1913, D. erythraeus Bezzi, 1905 and D. humeralis Zetterstedt, 1850 are recorded for the first time from Morocco and, except for the latter species, from North Africa as a whole. New faunistic data are given for five other species and two species are deleted from the list of Moroccan Bibionidae, D. febrilis (Linnaeus, 1758) and B. laufferi Strobl, 1906, as their previous records were based on erroneous identifications. The Moroccan fauna of Bibionidae includes at least 18 taxa, in contrast to 1–7 taxa known in the other North African countries. From a zoogeographical point of view, most of these taxa are West Palaearctic or Mediterranean elements generally also present in Southern Europe, while five of them are possible endemic Moroccan elements. One Afrotropical species, D. erythraeus, is recorded for the first time for the Palaearctic region as a whole. The hypothesis concerning the presence of this species north of the Sahara is discussed. A tentative key for the identification of Moroccan Bibionidae is proposed.